Gel and Molecular Properties of Waxy Rice Starch - Perdon, A.A.; Juliano, Bienvenido O. (Wiley, 1975)
The differences in the physicochemical properties of starch (amylopectin) from waxy rices from the Philippines, Japan, and Thailand differing in processed rice quality were investigated. Samples of waxy rice starch showed final birefringence end‐point temperature (BEPT) between 58 and 78°C. None of the samples showed BEPT values between 70 and 72°C. The gel viscosity values (measured with a Wells‐Brookfield viscometer) of samples with BEPT values above 70°C were higher than those of samples with BEPT values below 70°C. Sedimentation coefficient and intrinsic viscosity were positively correlated and showed a U‐shaped relationship with BEPT with minima at a BEPT of about 68°C. Differences in viscosity properties were mainly due to differences in the molecular weight of amylopectin, since the samples studied had similar mean chain lengths. BEPT was a useful index of amylopectin molecular weight in the waxy rice starch samples studied.